Use of Partial Range of Field Intraocular Lenses in Eyes with Macular Disease - Saad, Amr; Findl, Oliver; Kretz, Florian; Breyer, Detlev R. H. (Klinische Monatsblätter für Augenheilkunde, 2025)
This comprehensive review evaluates the current evidence and expert opinion regarding the use of extended depth of focus (EDOF) intraocular lenses (IOLs) in patients with macular disease. A literature review and a survey of European Society of Cataract and Refractive Surgeons (ESCRS) committee members were conducted. The review found a growing body of evidence suggesting potential benefits of EDOF IOLs in selected patients with mild to moderate macular disease, although concerns remain. The survey found that while 59% of respondents considered EDOF IOL implantation in this population “worth trying”, only 37% reported performing the procedure occasionally, and a minority did not consider it at all. Further research is needed to determine optimal patient selection criteria and long-term outcomes for EDOF IOLs in eyes with macular pathology.
Keywords: intraocular lens; extended depth of focus; macular disease; clinical decision making